Biodiversity patterns and environmental drivers of fragile alpine glacial lake ecosystems in the Himalaya: Implications for conservation and management - Muhammad Manzoor; Mushtaq Ahmad; Syed Waseem Gillani; Muhammad Waheed; Jussi Grießinger; Hamayun Shaheen; Wolfgang Jens-Henrik Meier (Ecological Indicators)
Alpine glacial lakes (AGLs) in the Himalayas as vital biodiversity hotspots, are under increasing pressure from climate change and human-driven disturbances. Nature-based solutions are an effective approach to mitigating stress from external factors and can enhance sustainable environmental protection. The unique traits of AGL vegetation in the alpine zone make it valuable for conservation and restoration planning. This study investigates the ecological dynamics of AGL vegetation along altitudinal gradients (2800–4500 m) in Himalaya, focusing on environmental drivers. A systematic quadrat sampling method was employed to sample vegetation attributes across 47 sites for the period July to September in 2023 and 2024, encompassing a total of 940 quadrats. We sub-classified the alpine lake habitats into low-altitude lakes (LAL), middle-altitude lakes (MAL), and high-altitude lakes (HAL). A total of 168 species from 44 families were recorded. Our findings indicated significant variations in floristic composition and distribution across altitude. Altitudinal categories exhibited notable differences in their diversity patterns, with HAL showing the highest Shannon’s diversity index (3.47 ± 0.04) but the lowest Simpson’s diversity index (0.04 ± 0.00), indicating lower species dominance. Additionally, HAL demonstrated greater evenness (0.86 ± 0.01) and dominance values (0.96 ± 0.00) compared to MAL and LAL. The βsim cluster analysis revealed that HAL represents 100 % species turnover, MAL exhibits intermediate turnover, and LAL shows significant species overlap. Seventeen indicator species were identified across the individual AGLs. CCA highlighted that various soil parameters such as K, N, and P, along with grazing and erosion, are key drivers of community composition. Pearson’s r-values indicated that HAL indicator species are more responsive to land use pressure, whereas LAL indicator species are more sensitive to soil properties. This study emphasizes the significance of AGL vegetation for the threatened plant diversity of the Himalayas and its implications for nature-based environmental management worldwide.